Exploring the “gene–protein–metabolite” network of coronary heart disease with phlegm and blood stasis syndrome by integrated multi-omics strategy - Yang, Guang; Zhou, Siyuan; He, Haoqiang; Shen, Zinuo; Liu, Yongmei; Hu, Jun; Wang, Jie (Frontiers in Pharmacology, 2022)
Background: In the theory of Traditional Chinese Medicine, Phlegm and Blood Stasis(PBS) is the pathological basis of coronary heart disease(CHD). The purpose of this study is to explore the biological basis of PBS Syndrome in CHD area. Methods: Using a strategy that integrated RNA-seq, DIA-based proteomics, and untargeted metabolomics on 90 clinic samples, we constructed a “gene-protein-metabolite” network for CHD-PBS Syndrome. We expanded the sample size and validated the differential genes and metabolite in the network by enzyme linked immunosorbent assay test. Results: Our study revealed that the "gene-protein-metabolite" network of CHD-PBS Syndrome includes 12 mRNAs, 4 proteins, and 14 metabolites. JNK1, FOS, CCL2, CXCL8, PTGS2, and CSF1 were all low expressed in the PBS group during the sequencing stage, whereas arachidonic acid (AA) was highly expressed. During the validation stage, JNK1, AP-1, CCL2, and CXCL8 were low expressed, whereas PTGS2, CSF1 and AA were highly expressed. The area under the receiver operating curve was as follows: CSF1 [0.9635, 95%CI (0.9295, 0.9976)] >JNK1 [0.9361, 95% CI (0.8749, 0.9972)] >CXCL8 [0.8953, 95% CI (0.8222, 0.9684)] > CCL2 [0.8458, 95% CI (0.7676, 0.9241)] >AP-1 [0.7884, 95%CI (0.6869, 0.8899)]. The logistic regression model composed of CSF1 and JNK1 had the greatest diagnostic value and significance for PBS Syndrome. Conclusion: PBS Syndrome is characterized by lower levels of FOS, AP-1, CCL2, CXCL8, and JNK1 and elevated levels of PTGS2 and CSF1, implying that arachidonic acid metabolism is abnormal and JNK/AP-1 pathway is inhibited. PBS Syndromes, as a subtype of CHD, may have unique molecular changes.